Optimized balance between crop productivity, restoration and maintenance of vital soil functions and soil carbon sequestration and storage – the SmartSOIL (FP7) project - Molnár, András (Acta Agraria Debreceniensis, 2012)
Soils provide the most indispensable function of supporting the production of food and feed for a growing human population. At the same time they provide a range of regulating and supporting functions related to climate change and removal of greenhouse gases. The majority of the soil functions are closely linked to the flows and stocks of soil organic carbon (SOC); low levels of both flows and stocks may seriously interfere with several of the essential soil functions and thus affect the ecosystem services that soils deliver. Soil degradation is considered a serious problem in Europe and a large part of the degradation is caused by intensive cultivation practices in agriculture. The aim of the SmartSOIL project is to link the results of different scientific fields through a holistic and multidisciplinary approach and as a result develop a decision making tool contributing to sustainable development.